Validation of Simplified Micro-models for the Static Analysis of Masonry Arches and Vaults. Issue 8 (3rd August 2021) - Alforno, M.; Monaco, A.; Venuti, F.; Calderini, C.
ABSTRACT: Compared to simple masonry walls, numerical modelling of masonry vaulted structures is particularly complex due to their three-dimensional curved geometry and articulated masonry pattern. Moreover, the scarce availability of experimental data makes it difficult to validate numerical models for these types of structures. Recently, the simplified micro-modelling approach has been applied by different authors, despite some intrinsic limits, such as huge numerical effort and adoption of ad-hoc written numerical codes. The aim of this study is to overcome these difficulties by using a commercial software with built-in friction interface models and to validate the proposed simplified-micro model through experimental tests on in-scale specimens of arch and cross vault. The proposed approach has shown promising features: experimental results have been numerically reproduced with a high degree of accuracy, both in case of planar and space structures, with both dry and mortar joints. The final result of the study is a validated modelling strategy that could be confidently applied to real masonry vaulted structures.